A-212 The Limitations of Hippocampal Volumetric Measurements on Clinical Decision-Making: A Case Study. (17th August 2022) - Kaser, Alyssa; Carlew, Anne; Denney, David; Nguyen, Trung; Ruchinskas, Robert
Abstract: Objective: Integrating multiple pieces of information is a well-known clinical challenge, especially in light of emerging technologies such as NeuroQuant, a fully-automated software used alongside magnetic resonance imaging (MRI) to quantify the volume of brain structures. Using population-based normative data, NeuroQuant compares measurements of certain neuroanatomical features to normal controls, providing metrics for structural abnormalities that may influence the concern for a suspected neurodegenerative etiology. Clinicians should be aware of potential confounding factors when incorporating this information into their clinical impression, as illustrated by this case. Method: We present a unique case study of a 71-year-old Black female who was followed with serial neurological, neuropsychological, and MRI with NeuroQuant evaluations over 10+ years. Results: The patient's early neuropsychological testing results, in combination with NeuroQuant volumetric measurements, raised suspicion for a potential neurodegenerative process and thereby influenced treatment decisions. However, on longitudinal follow-up, all clinical evaluations were stable except NeuroQuant measurements. From ages 69 to 71, the patient's hippocampal volumes respectively shifted from the < 5th to 61st normative percentile (see Table 1). Conclusion: Novel volumetric analyses should be interpreted with caution when formulating a clinical impression. Potential explanations for the observed change in NeuroQuant percentile include 1) an update to the normative database, 2) a software update, and 3) the patient moving normative age bands. As with neuropsychological testing, understanding the basis of scores produced by NeuroQuant and characteristics of the normative population is important, as this technology is increasingly used to direct clinical decision-making.